THE INFLUENCE OF DIGITAL MARKETING, MARKETING INNOVATION AND BUSINESS COMPETITIVENESS ON THE PERFORMANCE OF WOMEN'S MSMES IN BIREUEN DISTRICT - Rizkina Putri Mahmuddin; Ikramuddin; Jullimursyida; Naufal Bachri (RADJA PUBLIKA, 2025)
Micro, Small, and Medium Enterprises performance refers to the level of success or achievement of micro, small, and medium enterprises in achieving their business goals. This performance includes various aspects that reflect the success of MSMEs in operations, finance, marketing, and overall business growth. This study aims to test and analyze the influence of digital marketing variables, marketing innovation and business competitiveness on MSME performance in Bireuen Regency. The data used are primary data collected using questionnaires distributed to 144 female MSME actors in two sub-districts in Bireuen Regency. The data analysis tool uses multiple regression analysis with the SPSS version 25 program. The results of the study found that digital marketing variables, marketing innovation and business competitiveness have a significant effect on MSME performance in Bireuen Regency.